Law and the judiciary: Divides and dissent in Malaysia - Sharom, Azmi (Center for Southeast Asian Studies, Kyoto University, 2018)
Malaysia is a common law country, and as such the decisions of its courts have a binding and law-making force. This means that the Malaysian judiciary is highly influential in setting the tenor of governance. In this article I examine and analyze some key decisions that had an influence on divisiveness and dissent in the country. I point out that the courts have been poor in ensuring that the legal system protects the nation from divisive elements, and the legal system does not do enough to guarantee the fundamental rights and democratic principles that were envisioned by the founding fathers for the citizenry. The article closes with an attempt to understand why this is the case.